2008
DOI: 10.1017/s0958344008000219
|View full text |Cite
|
Sign up to set email alerts
|

English vocabulary learning with word lists, word cards and computers: implications from cognitive psychology research for optimal spaced learning

Abstract: The spacing effect is known to be one of the most robust phenomena in experimental psychology, and many attempts have been made to realize effective spaced learning for L2 vocabulary learning. This study compares vocabulary learning with word lists, word cards, and computers in order to identify which material leads to the most superior spaced learning. In the experiment, 226 Japanese high school students studied ten English words with one of the three learning materials: lists, cards, and computers. One-way a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 21 publications
6
74
1
13
Order By: Relevance
“…repetition. It was confirmed that learning vocabulary through flash card would lead to better learning than traditional method (Mondria & Mondria-de Vries, 1994;Nakata, 2008;Schmitt & Schmitt, 1995), so this study was in line with their statement and findings.…”
Section: A Research Question Onesupporting
confidence: 83%
“…repetition. It was confirmed that learning vocabulary through flash card would lead to better learning than traditional method (Mondria & Mondria-de Vries, 1994;Nakata, 2008;Schmitt & Schmitt, 1995), so this study was in line with their statement and findings.…”
Section: A Research Question Onesupporting
confidence: 83%
“…Nonetheless, many studies on the use of CMC and ICT (information communication technology) for vocabulary teaching and learning reveal that CMC and ICT contribute to a considerable level of learning new vocabulary and enhance students' vocabulary knowledge. Based on his study of vocabulary learning with word lists, word cards, and computers, Nakata (2008) discovers that high school students experience a far more effective spaced learning of second language vocabulary via computers due to their higher retention rate of words learnt than lists, as well as the positive effect exerted by the computers on the students' motivation to learn vocabulary. As for CMC environments, they allow teachers to "tailor guidance and feedback to individual learner's needs and scaffold the use of new forms, vocabulary items, and language functions when the opportunity to do so presented itself in online conversations" (Meskil & Anthony, 2005, p. 102).…”
mentioning
confidence: 99%
“…Learners are given a model of the target language behavior, as well as specific practice in manipulating key language items. The actual pedagogic task, a simulation, is also consistent with research on the facilitative effects of classroom interaction (Nakata, 2008). Most tasks take as their point of departure input data of some sort.…”
Section: Literature Reviewmentioning
confidence: 65%